Analisis Yuridis Terhadap Perlindungan Ekspresi Budaya Tradisional Provinsi Gorontalo - Mohammad Abdi Lanjahi; Fenty U Puluhulawa; Novendri M. Nggilu; Ahmad Ahmad (Universitas Sains dan Teknologi Komputer, 2023)
Gorontalo Province is an area rich in traditional culture. Protection of Traditional Cultural Expressions in Gorontalo has been regulated in Regional Regulation (Perda) Number 7 of 2017. This regulation also regulates protection of Traditional Cultural Expressions of Gorontalo Province. This study aims to find out how the Traditional Cultural Expressions of the people of Gorontalo Province are Protected and to find out the roles and responsibilities of the local government for the Protection of the Traditional Cultural Expressions of the people of Gorontalo Province. Researchers use this type of normative research. Namely the type of legal research that places law as a building system of norms. The process of collecting data from research objects is using primary, secondary and tertiary data. The data obtained was then processed using qualitative analysis by describing analytically and prescriptively descriptively. The results of the research found: (1) The protection of traditional cultural expressions in Gorontalo has been regulated in Regional Regulation Number 7 of 2017. This regional regulation has not been fully effective in providing protection for traditional cultural expressions. It can be seen from the data obtained that there are still 20 Gorontalo cultures that have been included in the preparation of recording and documentation but are not attached to the regional regulation. (2) The Provincial Government of Gorontalo has carried out its roles and responsibilities in efforts to protect cultural expressions by recording and documenting as well as outreach. However, in reality this is not enough to maintain Gorontalo's cultural wealth. One example is the absence of an art building that the government should pay attention to to build so that cultural heritage and its protection can be maintained.